1992
DOI: 10.1159/000154630
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking of the Apical Electrogenic H Pump in Isolated Malpighian Tubules <i>(Formica polyctena</i><i>)</i>by the Use of Barium

Abstract: In the present study evidence is given for the presence of an electrogenic, vacuolar type ATPase (V type ATPase) in the apical membrane of malpighian tubules of Formica. Barium (6 mM), the metabolic inhibitor monoiodo-acetic acid (MIA; 5 10-4M) and two inhibitors of V type proton ATPases, i.e. bafilomycin A1 (Baf-A1; 5·10-6M) and N-ethylmaleimide (NEM; 5 10–4M), all inhibited fluid secretion significantly (p < 0.05). This is in agreement with the hypothesis that K enters passiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 14 publications
1
24
2
Order By: Relevance
“…Similarly, blockage of K + currents by prior exposure K + -free saline did not block the effect of Ba 2+ on the basolateral membrane potential. This result indicates that the current responsible for the hyperpolarization is not carried by K + , in contrast to proposals for tubules of F. polyctena and A. aegypti Pannabecker et al, 1992;Weltens et al, 1992;Masia et al, 2000). On the other hand, prior exposure to Cl --free saline containing 20·mmol·l -1 K + blocked the hyperpolarization of Vbl in response to Ba 2+ .…”
Section: The Effect Of Ba 2+ On Vbl: a Role For Basolateral CL -Channelscontrasting
confidence: 63%
See 2 more Smart Citations
“…Similarly, blockage of K + currents by prior exposure K + -free saline did not block the effect of Ba 2+ on the basolateral membrane potential. This result indicates that the current responsible for the hyperpolarization is not carried by K + , in contrast to proposals for tubules of F. polyctena and A. aegypti Pannabecker et al, 1992;Weltens et al, 1992;Masia et al, 2000). On the other hand, prior exposure to Cl --free saline containing 20·mmol·l -1 K + blocked the hyperpolarization of Vbl in response to Ba 2+ .…”
Section: The Effect Of Ba 2+ On Vbl: a Role For Basolateral CL -Channelscontrasting
confidence: 63%
“…Equivalent circuit analysis shows that increasing basolateral membrane resistance with Ba 2+ will cause the loop current to drive the basolateral membrane potential more negative Pannabecker et al, 1992;Weltens et al, 1992;Masia et al, 2000;Wiehart et al, 2003b). In F. polyctena and A. aegypti tubules it has been proposed that the loop current is carried by inward K + flow through basolateral K + channels Weltens et al, 1992;Masia et al, 2000).…”
Section: The Effect Of Ba 2+ On Vbl: a Role For Basolateral CL -Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…-cotransporter (Ianowski and O'Donnell, 2004) and barium-sensitive potassium channels (Beyenbach and Masia, 2002;Masia et al, 2000;Weltens et al, 1992); their relative importance may vary between insects. Present estimates suggest that, in Drosophila, each contributes approximately equally to the K + flux (Torrie et al, 2004).…”
mentioning
confidence: 99%
“…11,41,49 Several studies evidence the presence of a cotransport system and a H + pump in the MTs of Formica polyctena (Hymenopera, Formicidae). [50][51][52][53][54] The presence of active and passive K + uptake mechanisms across the basal membrane was investigated in different bath K + concentrations. The authors proposed a model in which K + channels play a dominant role in high-K + bathing medium, and the results obtained from intracellular and luminal ion-selective measurements have demonstrated that the calculated gradients for Cl 2 and K + are consistent with the transport mechanisms.…”
Section: Physiologymentioning
confidence: 99%